Design and fabrication of micro imaging lens for biomedical applications - Seyed Mohhammad Mirkhalaf Valashani (2011)
In this research, a hot compression molding apparatus was designed and fabricated for production of polymer micro stand-alone lens. The fabricated lens can be installed easily on the tip of a fiber optic imaging purposes. FEM (Finite Element Method) simulation of the forming process was conducted to optimize the processing parameters and to predict the behaviour of polycarbonate (PC) under different molding temperatures. The results of FEM simulation were then used to compare the actual experimental results. Design of experiments was used to locate the actual feasible molding window.